Circular polarization in relativistic jets - Macquart, Jean-Pierre (Elsevier, 2003)
Circular polarization is observed in some relativistic jet sources at radio wavelengths. It is largely associated with activity in the cores of the radio sources, is highly variable, and is strongest during ejection episodes. VLBI imaging and interstellar scintillation arguments show that the degree of circular polarization is as high a few percent in some sources, and is associated with milliarcsecond and microarcsecond source structure. The circular polarization most likely originates as a result of conversion of linear polarization in the relativistic plasma surrounding the source. However, cyclotron orsynchrotron emission can account for the magnitude of the circular polarization observed in some Galactic jet sources.